ANALYSING DUPES - ALGORITHM TO DETECT AND PREVENT DOS ATTACK - 528, Er. Sandeep Singh Khehra, Ms.Rimpi Rani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the last three decades, the number of people using the Internet has exploded, and ecommerce sites, search engines, and online banking have all become indispensable components of today's world. The key issues that plague the Internet are application security and availability. DoS attacks are a serious attack when it comes to availability. It prevents the intended user from accessing resources or services. The DoS attack has extremely hazardous consequences. A denial of service attack occurs when attackers send a high number of spam or copy solicitations to a server, delivering it inaccessible to other people or real clients. The Computer Emergency Response Team arranges refusal of administration assaults into three sorts. The main class was worried about asset usage, like organization data transfer capacity or CPU utilisation.. In this paper, the DUPES algorithm is introduced and developed to improve the security of MAC spoof DoS assaults. To protect against start frame and logoff frame DoS attacks, four alternative approaches were established. To test DUPES' performance, the number of clients is increased. When the number of clients grows, the most dangerous attack is the start frame attack. However, the packet delivery ratio, throughput, and packet drop measurement all show a decrease in performance.